Python for Geeks - Asif, Muhammad (Packt Publishing, 2021)
Take your Python skills to the next level to develop scalable, real-world applications for local as well as cloud deployment Key Features All code examples have been tested with Python 3.7 and Python 3.8 and are expected to work with any future 3.x release Learn how to build modular and object-oriented applications in Python Discover how to use advanced Python techniques for the cloud and clusters Book Description Python is a multipurpose language that can be used for multiple use cases. Python for Geeks will teach you how to advance in your career with the help of expert tips and tricks. You'll start by exploring the different ways of using Python optimally, both from the design and implementation point of view. Next, you'll understand the life cycle of a large-scale Python project. As you advance, you'll focus on different ways of creating an elegant design by modularizing a Python project and learn best practices and design patterns for using Python. You'll also discover how to scale out Python beyond a single thread and how to implement multiprocessing and multithreading in Python. In addition to this, you'll understand how you can not only use Python to deploy on a single machine but also use clusters in private as well as in public cloud computing environments. You'll then explore data processing techniques, focus on reusable, scalable data pipelines, and learn how to use these advanced techniques for network automation, serverless functions, and machine learning. Finally, you'll focus on strategizing web development design using the techniques and best practices covered in the book. By the end of this Python book, you'll be able to do some serious Python programming for large-scale complex projects. What you will learn Understand how to design and manage complex Python projects Strategize test-driven development (TDD) in Python Explore multithreading and multiprogramming in Python Use Python for data processing with Apache Spark and Google Cloud Platform (GCP) Deploy serverless programs on public clouds such as GCP Use Python to build web applications and application programming interfaces Apply Python for network automation and serverless functions Get to grips with Python for data analysis and machine learning Who this book is for This book is for intermediate-level Python developers in any field who are looking to build their skills to develop and manage large-scale complex projects. Developers who want to create reusable modules and...